High resolution beta-NMR study of (8)Li(+) implanted in gold - Parolin, T; Salman, Z; Chow, K; Song, Q; Valiani, J; Saadaoui, H; O'Halloran, A; Hossain, MD; Keeler, T; Kiefl, R; Kreitzman, SR; Levy, C; et al. (2008)
We report the behavior of low energy L8 i+ implanted into gold as revealed by beta-detected NMR. At an external magnetic field of 3 T, two narrow resonances are observed, which are attributed to Li in the octahedral interstitial and the substitutional lattice sites. The Knight shifts for these two resonances are found to be temperature independent with values of +141 (4) and +73 (5) ppm, respectively. The spin-lattice relaxation rate in high magnetic fields at 290 K is slow, consistent with the Korringa relation; however, the rate increases dramatically for magnetic fields below about 2 mT. We attribute this to interaction of the L8 i spin with the host lattice nuclear spins. © 2008 The American Physical Society.